Aunt Jane's Nieces on the Ranch - Baum, L. Frank (Lyman Frank), 1856-1919 (Salt Lake City, UT : Project Gutenberg, 2011)
"Aunt Jane's Nieces on the Ranch" by L. Frank Baum is a novel published in 1913. On a California ranch, progressive owners Arthur and Louise Weldon hire a Mexican governess named Inez to care for their baby daughter. When Louise's uncle disapproves and brings an American nurse instead, tensions rise. Inez grows possessive of the child as mysterious sounds echo through the old Spanish estate's secret passages. Some believe the house is haunted, but hidden connections may explain the strange occurrences. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Aunt_Jane%27s_Nieces_on_the_Ranch
Release date is 2011-04-12
Roger Frank and the Online Distributed Proofreading Team at http://www.pgdp.net.
Keywords: Mystery and detective stories; Ranch life -- Juvenile fiction; California -- Juvenile fiction; Families -- Juvenile fiction; Young women -- Social life and customs -- Juvenile fiction; Infants -- Juvenile fiction